P11.32.A EGFR expression and non-methylated MGMT predict distant recurrence in glioblastoma patients treated with standard therapy. (5th September 2022) - Urup, T; Trip, A K; Chiranth, S B; Christensen, I J; Grunnet, K; Møller, S; Hasselbalch, B; Muhic, A; Lassen, U; Poulsen, H S
Abstract: Background: Infiltrative growth within the central nervous system is hallmark of glioblastoma (GBM) at time of diagnosis. Targeting infiltrative glioma cells by adding chemotherapy to local treatment (surgical resection and radiotherapy) has led to improved tumor control and survival. Still, infiltrative growth is a major factor in therapeutic failure and tumor recurrence is almost inevitable. Herein, we hypothesize that distant recurrence represents a more migratory phenotype and that biomarkers associated with distant recurrence can be used to personalize the treatment. The aim of this study was to identify clinical and molecular factors associated with distance recurrence in glioblastoma patients treated with standard therapy. Material and Methods: A prospective cohort of consecutive, non-selected GBM patients administered standard therapy as primary treatment between 2005-2020 at Rigshospitalet, Copenhagen, Denmark. Distant recurrence was defined as a new contrast-enhancing tumor lesion outside the radiation field (> 2 cm from the gross tumor volume). Clinical and molecular factors were screened for association with time to distant recurrence (p < 0.30) using univariate analysis. The final model was generated employing multivariate Cox regression analysis to model the association with time to distant recurrence. It was chosen to maintain known prognostic factors in the model and subsequently add significantly associated factors (p < 0.05). Competing risk adjusted analysis were performed with death as a competing risk. Results: A total of 897 patients were included and at a median follow-up time of 73 (range: 12-198) months, 733 patients were evaluable for recurrence pattern. Out of 733 patients, 146 patients (20%) had distant recurrence. Median time to tumor progression was 7.0 months for patients with a local recurrence and 8.0 months for those with a distant recurrence (p=0.31). The following prognostic factors were not associated with distant recurrence by multivariate analysis: Corticosteroid use (p=0.84), age (p=0.20), multifocal disease (p=0.81), ECOG performance status (p=0.99) and degree of tumor resection (p=0.20). In multivariate analysis, factors independently associated with a higher likelihood of distant recurrence were: Non-methylated promoter of the MGMT gene (HR=1.93; 95% CI: 1.27-2.95; p=0.002) and positive expression of Epidermal Growth Factor Receptor (EGFR) by immunohistochemistry (HR=3.70; 95% CI: 1.61-8.33; p=0.002). Conclusion: Non-methylated MGMT and positive expression of EGFR were independently associated with a higher likelihood of distant recurrence in GBM patients treated with standard-of-care. These factors, if validated, can be used for risk stratification and to enrich clinical treatment protocols aiming at improved local or distant tumor control.